FRA EKSPEDITION TIL FELTARBEJDE - Ferdinand, Klaus (Tidsskriftet Antropologi, 1997)
Klaus Ferdinand: From Expedition to Fieldwork In 1945 the study of ethnography (cultural anthropology) started at Copenhagen University under Dr. Kaj Birket-Smith, head curator at the Department of Ethnography, the Danish National Museum. The post-war years were a period of great expectations and enthusiasm, but of little money. Early ethnographical field experiences often took place within archaeological or natural science expeditions; later, after the establishment of The Danish State Research Foundation in 1952, they were followed by a few ethnographical expeditions, that is, before individual fieldwork became the rule. The article surveys these developments, coloured by the author’s own experiences, changing theoretical orientations and methodologies.